Ontario Brain Injury Association Peer Support Program: a mixed methods protocol for a pilot randomised controlled trial. Issue 3 (23rd March 2019) - Munce, Sarah E P; Jaglal, Susan; Kastner, Monika; Nelson, Michelle L A; Salbach, Nancy M; Shepherd, John; Sweet, Shane N; Wilcock, Ruth; Thoms, Carla; Bayley, Mark T
Abstract : Introduction: The objective of this study is to conduct a pilot randomised controlled trial (RCT) of the Ontario Brain Injury Association (OBIA) Peer Support Program. The RCT is designed to evaluate the effectiveness and dose–response of the Peer Support Program in improving participation and mood for people with moderate-to-severe traumatic brain injury compared with a wait-list control group. Methods and analysis: The proposed research is a three-phase, mixed methods pilot RCT. Consistent with an integrated knowledge translation approach, the study design has been informed in consultation with the knowledge user (ie, OBIA). It will include an initial qualitative examination of barriers and enablers to the trial implementation (phase 1), a pilot RCT (phase 2) and conclude with a qualitative component (phase 3). A qualitative descriptive approach will be adopted for both qualitative phases of the study (n=20–25) and thematic analysis will be used. The 6 months phase-2 trial will be conducted with 60 participants. These participants will be randomised to one of three groups: a twice a week programme (n=20), a once a week programme (n=20) or the wait-list control group (n=20). The feasibility of participant recruitment and retention, data collection, as well as participant adherence to the OBIA Peer Support Program will be evaluated. The primary outcome measure will be participation, as measured by the Participation Assessment with Recombined Tools–Objective. Other proposed outcomes of interest will include mood, health-related quality of life and self-efficacy. Ethics and dissemination: Ethics approval will be obtained from the principal author's institution (University Health Network Research Ethics Board). The results of this study will inform the development of a larger scale RCT and will inform future iterations of the OBIA Peer Support Program including a revised programme curriculum. Trial registration number: NCT03450460; Pre-results.